Shallow subtidal marine benthic communities of Nachvak Fjord, Nunatsiavut, Labrador: A glimpse into species composition and drivers of their distribution. - Alan M Friedlander; Enric Ballesteros; Alyssa M Adler; Whitney Goodell; Ryan Jenkinson; Jennie A Knopp; Christopher D H Thompson; Molly Timmers; Cameron A J Walsh; Enric Sala (PLoS ONE, 2023)
Marine fjords along the northern Labrador coast of Arctic Canada are influenced by freshwater, nutrients, and sediment inputs from ice fields and rivers. These ecosystems, further shaped by both Atlantic and Arctic water masses, are important habitats for fishes, marine mammals, seabirds, and marine invertebrates and are vital to the Labrador Inuit who have long depended on these areas for sustenance. Despite their ecological and socio-cultural importance, these marine ecosystems remain largely understudied. Here we conducted the first quantitative underwater scuba surveys, down to 12 m, of the nearshore marine ecology of Nachvak Fjord, which is surrounded by Torngat Mountains National Park located in Nunatsiavut, the Indigenous lands claim region of northeastern Canada. Our goal was to provide the Nunatsiavut Government with a baseline of the composition and environmental influences on the subtidal community in this isolated region as they work towards the creation of an Indigenous-led National Marine Conservation Area that includes Nachvak Fjord. We identified four major benthic habitat types: (1) boulders (2) rocks with sediment, (3) sediment with rocks, and (4) unconsolidated sediments, including sand, gravel, and cobble. Biogenic cover (e.g., kelp, coralline algae, and sediment) explained much of the variability in megabenthic invertebrate community structure. The kelp species Alaria esculenta, Saccharina latissima, and Laminaria solidungula dominated the boulder habitat outside of the fjord covering 35%, 13%, and 11% of the sea floor, respectively. In contrast, the middle and inner portions of the fjord were devoid of kelp and dominated by encrusting coralline algae. More diverse megabenthic invertebrate assemblages were detected within the fjord compared to the periphery. Fish assemblages were depauperate overall with the shorthorn sculpin, Myoxocephalus scorpius, and the Greenland cod, Gadus ogac, dominating total fish biomass contributing 64% and 30%, respectively. Understanding the composition and environmental influences within this fjord ecosystem not only contributes towards the protection of this ecological and culturally important region but serves as a baseline in a rapidly changing climatic region.